2022
DOI: 10.3390/polym14142958
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Injection Molded PP/PET-Nanofibril Composites and Foams

Abstract: The creation and application of PET nanofibrils for PP composite reinforcement were studied. PET nanofibrils were fibrillated within a PP matrix using a spunbond process and then injection molded to test for the end-use properties. The nanofibril reinforcement helped to provide higher tensile and flexural performance in solid (unfoamed) injection molded parts. With foam injection molding, the nanofibrils also helped to improve and refine the microcellular morphology, which led to improved performance. Easily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…First, PET nanofibrils can enhance the heterogeneous nucleation efficiency at interfaces, which improves cell nucleation. Second, PET fibrils can not only promote the viscoelasticity and strain hardening behavior of PP [ 48 ], but also increase the crystallization rate, which in turn improves the melt strength of PP in relatively high temperature. Both reasons can contribute to the reduction of cell coalescences and collapses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, PET nanofibrils can enhance the heterogeneous nucleation efficiency at interfaces, which improves cell nucleation. Second, PET fibrils can not only promote the viscoelasticity and strain hardening behavior of PP [ 48 ], but also increase the crystallization rate, which in turn improves the melt strength of PP in relatively high temperature. Both reasons can contribute to the reduction of cell coalescences and collapses.…”
Section: Resultsmentioning
confidence: 99%
“…For one thing, the refined crystals caused by PET fibrils can promote the flexibility and toughness of PP matrix. Due to the weak cohesive forces between PET molecular chains, the PET fibrils can enhance the sliding ability of PP crystals [ 48 ]. Previous studies have demonstrated that PET nanofibrils could induce flexible transcrystalline layers around them, leading to greatly improvement of the interfacial adhesion between PET nanofibril and polymer matrix [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with PP/PET(F) composite, the average diameter of PET fibrils remains at 270 nm, but the proportion of the fibrils distributed in 100~250 μm is increased. These results indicate that the incorporation of PDPP particles has no negative effect on the formation of PET nanofibrils and can generally effectively improve the microcellular foaming properties [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pure PP exhibits huge, regular-like polygonal shapes with closed cell structures. The introduction of spherical PET domains endows a reduction in cell size, an increase in cell density, and an improvement in cell homogeneity due to the heterogeneous cell nucleation effect [ 35 ]. After PET domains transformed from spherical droplets to fibrils, the cell size became much smaller and cell density increased dramatically.…”
Section: Resultsmentioning
confidence: 99%
“…This significant interest is due to the remarkable properties of polymeric nanocomposite materials compared to the current polymers and conventional macro- or micro-composites [ 1 ]. The properties of polymeric nanocomposites (much improved over those conventional materials) refer to elasticity [ 2 , 3 , 4 , 5 , 6 , 7 ], mechanical resistance, thermal resistance [ 8 ], low gas permeability [ 9 , 10 , 11 , 12 , 13 , 14 ], flammability [ 15 , 16 , 17 , 18 , 19 ], and a high degree of degradability [ 20 ].…”
Section: Introductionmentioning
confidence: 99%